2004
DOI: 10.1111/j.1468-1331.2004.00813.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose riboflavin treatment is efficacious in migraine prophylaxis: an open study in a tertiary care centre

Abstract: The aim of this study was to investigate the efficacy of riboflavin for the prevention of migraine. An open label study was performed in a specialized outpatient clinic. Patients received 400 mg riboflavin capsules per day. Headache frequency, duration, intensity and the use of abortive drugs were recorded at baseline and 3 and 6 months after treatment. Headache frequency was significantly reduced from 4 days/month at baseline to 2 days/month after 3 and 6 months (P < 0.05). The use of abortive drugs decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(108 citation statements)
references
References 10 publications
6
97
1
4
Order By: Relevance
“…In clinical trials riboflavin was described as an alternative agent in the prophylactic anti-migraine treatment (Boehnke et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In clinical trials riboflavin was described as an alternative agent in the prophylactic anti-migraine treatment (Boehnke et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that a cascade of oxidizing events triggered (or inhibited) during the peritransplant period can have profound long-term consequences for a cardiac graft. Whether or not this might be of any therapeutic utility remains a subject of conjecture, but clinical studies have reported that high-dose riboflavin appears to be safe, without long-term toxicity, and has relatively few adverse effects (8,28). These findings argue for the clinical study of a peritransplant antioxidant strategy as being one that is simple, safe, inexpensive, and potentially efficacious.…”
Section: Discussionmentioning
confidence: 99%
“…Good sources of riboflavin include wheat flour and bread, dairy products, eggs, nuts, green vegetables, and meat. An earlier study reveals that riboflavin could reduce migraine attack frequency [37].…”
Section: Vitamin Bmentioning
confidence: 99%